Proposta de harmonização da terminologia designativa de área e subáreas do Português como Língua Não Materna baseada em corpus - Lisboa, Joel Victor Reis (2021)
This research aims to propose a formal and conceptual terminological harmonization for the designative terminology of the area and subareas of Portuguese for Speakers of Other Languages (PSOL). Our motivations arose from the identification of a high formal variation of specialized phraseological units (SPUs) used to designate the area and subareas, as well as fundamental concepts of the PSOL area. In addition to the formal variation, we also noticed that some concepts and SPUs are defined in different and sometimes contradictory ways in different publications, while sometimes the same definition is used as a reference for two different SPUs. Therefore, based on the theoretical framework of Terminology and the methodological principles of Corpus Linguistics, we developed a terminological harmonization proposal aiming to contribute to the optimization and precision in the articulation and use of SPUs as well as their fundamental concepts. To propose the terminological harmonization, we carried out the following methodological procedures: (i) planning and compilation of a corpus of PSOL area publications; (ii) sample corpus selection and preparation for processing by WordSmith Tools 6.0 (SCOTT, 2012); (iii) identification and listing of candidates for designative SPUs and AAs (abbreviations and acronyms), including their formal variations; (iv) semasiological analyzes of the designative SPUs and AAs; (v) discussion of formal variation and election of standard SPUs and AAs; (vi) discussion of SPUs/AAs fundamental concepts and the conceptual variation identified; (vii) formation and suppression of conceptual equivalences, aiming to reduce cases of synonymy, homonymy, ambiguity, polysemy, and variations. As a result, five designative SPUs of PSOL area and its subareas, as well as five designative SPUs of fundamental concepts for the conception and delimitation of the area itself and its subareas were elected and appropriately harmonized, both formally and conceptually. Furthermore, we elected ten AAs representing each of the elected SPUs. In this harmonization proposal, we sought to locate the target concepts in the conceptual system of the area, highlight their conceptual limits, their distinctive characteristics and the logical relationships between the target concepts, as well as to characterize PSOL’s subareas, their target audience and their operation contexts.